STRATEGI BAURAN PEMASARAN PRODUK PEMBIAYAAN AKAD TAQSITH DALAM MENINGKATKAN JUMLAH ANGGOTA - Fadil Yahya; Hasan Sultoni; Mei Santi (JSE: Jurnal Sharia Economica, 2024)
Abstract The aim of this research is to study how to apply the Marketing Mix Strategy to taqsith financing products at the Indonesian Syirkah Muslim Cooperation. We know that cooperative competition is very competitive. If you are a little careless, you will definitely be left behind by other cooperatives if you don't do something innovative. One of the factors that cooperatives can use to fight competition in increasing the number of customer members is by implementing a Marketing Mix Strategy which consists of 7Ps (Product, Price, Place, Promotion, People, Process, Physical Evidence). It is hoped that implementing a marketing mix strategy can increase KSMI Tulungagung members. The research method that the researcher used was a qualitative approach. Data collection techniques were carried out using observation, interviews and documentation related to the research. The research results show that implementing the 7P marketing mix strategy can have an impact, namely increasing the number of customer members of the Tulungagung Indonesian Muslim Syirkah Cooperative. Keywords: Marketing Mix, Cooperatives, Customers, Marketing Strategy, Taqsith Financing.